ОЦЕНКА Состояния вегетативной нервной системы у подростков - Мамбеткаримов, Гайрат Абдикаримович; Танирбергенова, Арзыгул Курбанбаевна; Турманова, Паруаз Махмудовна (Медицина: теория и практика, 2020)